Status assessment and probabilistic health risk modeling of polycyclic aromatic hydrocarbons (PAHs) in surface soil across China - He, Mingjiang; Shangguan, Yuxian; Zhou, Zijun; Guo, Song; Yu, Hua; Chen, Kun; Zeng, Xiangzhong; Qin, Yusheng (Frontiers in Environmental Science, 2023)
Polycyclic aromatic hydrocarbon (PAH) accumulation in topsoil is getting particular concern with the rapid development of urbanization and industrialization, while the overall pollution status and related risk posed by PAHs received limited attentions at the national scale. This study conducted an overview of published data on 16 priority control PAHs by USEPA on the related peer-reviewed 207 research papers between 2000 and 2020 in 30 provinces of China. Based on that, the pollution levels, composition status, spatial distribution pattern, ecological risk, and human health risk posed by soil PAHs were evaluated. Monte Carlo simulation was adopted to model the probabilistic health risk and identify the contributor of such risks. Results demonstrated the concentrations of ∑16PAHs in soil varied from “undetected” to 261 μg g−1 with a mean value of 0.63 μg g−1, indicating the obvious accumulation of PAHs in topsoil of most provinces in China compared with the guideline value (0.2 μg g−1). The concentrations of ∑16PAHs in surface soil of China has obvious regional characteristics. Higher concentrations of soil PAHs are mainly distributed in north, northwest, and eastern regions, especially in Xinjiang, Shandong, Jiangsu, Sichuan, and Guangxi Provinces. Risk assessment indicates potential ecological and human health risk were posed by soil PAHs, therefore, reducing soil PAHs concentration and exposure frequency are the most effective pathways to protect human health. Despite the fact that risks posed by soil PAHs are generally low, concentrations of PAHs in some sites are relatively high. It is necessary to take effective measures to remediate soil PAHs pollution in certain areas to reduce concentration and associated risks.